Convergence - Córdova, Zoraida (Star Wars: the high Republic., 2022)
The next adventure in the High Republic begins expanding the new era of Star Wars, with a story set generations before Light of the Jedi. It is an age of exploration. Jedi travel the galaxy, expanding their understanding of the Force and all the worlds and beings connected by it. Meanwhile, the Republic, led by its two chancellors, works to unite worlds in an ever-growing community among near and distant stars. On the close-orbiting planets of Eiram and E'ronoh, the growing pains of a galaxy with limited resources but unlimited ambition are felt keenly. The two worlds' hatred for each other has fueled half a decade of escalating conflict and now threatens to consume surrounding systems. The last hope for peace emerges when heirs from the planets' royal families plan to marry. Before lasting peace can be established, an assassination attempt targeting the couple tilts Eiram and E'ronoh back into all-out war. To save both worlds, Jedi Knight Gella Nattai volunteers to uncover the culprit, while Chancellor Kyong appoints her own son, Axel Greylark, to represent the Republic's interests in the investigation. But Axel's deep distrust of the Jedi sparks against Gella's faith in the Force. She's never met such a puffed-up, privileged party boy, and he's never met a more self-serious, relentless do-gooder. The harder they work to untangle the shadowy web of the investigation, the more complicated the conspiracy appears to be. With accusations flying and potential enemies in every shadow, the pair will have to work together to have any hope of bringing the truth to light and saving both worlds.